Numerical Simulation Research on Well Pattern Optimization in High–Dip Angle Coal Seams: A Case of Baiyanghe Block - Wang, Hongli; Zhang, Xiao; Zhang, Suian; Huang, Hongxing; Wang, Jun (Frontiers in Earth Science, 2021)
The Baiyanghe block in Fukang, Xinjiang, China, is rich in coalbed methane (CBM) resources, and several pilot, experimental wells have yielded high production. Due to the high dip angle of the coal seam in this area, between 35–55°, the lack of understanding of the geological characteristics, the physical properties of coal, and gas–water migration law lead to immature development techniques and poor overall development benefits. We first conducted desorption and adsorption tests on low-rank coal of this area and found residual gas in the coal. We established a coalbed methane desorption model suitable for this area by modifying the isotherm adsorption model. Next, by analyzing the influence of the gas–water gravity differentiation in the high dip angle coal seam and the shallow fired coalbed methane characteristics in this area, we discovered the leakage of CBM from the shallow exposed area of the coal seam. Given the particular physical property of coal and gas–water migration characteristics in this area, we established the development of a well pattern model: (i) a multi-stage fracturing well in the floor of coal for water production; (ii) U-shaped along-dip direction horizontal wells in coal seams for gas production; (iii) vertical wells to capture CBM leakage. Using numerical simulation and net present value economics models, we optimized the well pattern's details. Applying our CBM desorption model, the numerical simulator can improve the accuracy of the low-rank coalbed methane productivity forecast. Applying the optimized well pattern, we improve the production capacity of CBM and reduce the waste of resources caused by leakage of CBM effectively.